Ammonia toxicity to the brain. Issue 4 (30th October 2012) - Braissant, Olivier; McLin, Valérie A.; Cudalbu, Cristina
Abstract: Hyperammonemia can be caused by various acquired or inherited disorders such as urea cycle defects. The brain is much more susceptible to the deleterious effects of ammonium in childhood than in adulthood. Hyperammonemia provokes irreversible damage to the developing central nervous system: cortical atrophy, ventricular enlargement and demyelination lead to cognitive impairment, seizures and cerebral palsy. The mechanisms leading to these severe brain lesions are still not well understood, but recent studies show that ammonium exposure alters several amino acid pathways and neurotransmitter systems, cerebral energy metabolism, nitric oxide synthesis, oxidative stress and signal transduction pathways. All in all, at the cellular level, these are associated with alterations in neuronal differentiation and patterns of cell death. Recent advances in imaging techniques are increasing our understanding of these processes through detailed in vivo longitudinal analysis of neurobiochemical changes associated with hyperammonemia. Further, several potential neuroprotective strategies have been put forward recently, including the use of NMDA receptor antagonists, nitric oxide inhibitors, creatine, acetyl‐L‐carnitine, CNTF or inhibitors of MAPKs and glutamine synthetase. Magnetic resonance imaging and spectroscopy will ultimately be a powerful tool to measure the effects of these neuroprotective approaches.